205 Innovative use of syndromic surveillance system for injury prevention and practice. (20th November 2022) - Waller, Anna; Proescholdbell, Scott; Ising, Amy
Abstract : Context: Injury prevention requires data to inform policy and practice through surveillance, research and evaluation. NC DETECT, a syndromic surveillance system originally developed for bioterrorism and infectious disease identification and response, provides timely, population-based data for injury prevention efforts. Purpose: We use this system to monitor and respond to both long-standing prevalent injury issues and emerging threats, including COVID-19's impact on injury. Process: Established in 2002 and legislatively mandated in 2005, NC DETECT uses statewide near-real-time emergency department (ED) and EMS data for North Carolina, USA (population >10.5 million). Data are available to users through a Web-based portal that includes options to generate custom data reports and personalize data dashboards. Targeted injury reports are sent to public health practitioners and prevention partners. New surveillance case-definitions and reports are added within hours of a request. Analysis: Statewide, all 24/7, acute care, civilian, hospital-affiliated EDs (currently N=130) submit data 3-times daily, while all EMS encounters are submitted daily. Over 4.5 million ED visits and over 1.5 million EMS encounters are added to NC DETECT each year. Outcomes: NC DETECT informs prevention efforts related to road safety, falls, overdose, violence, suicide, firearms, disaster response and climate resiliency. Weekly reports track trends for heat-related illness during summer months, monthly reports help counties monitor opioid overdoses and evaluate community-based interventions, and NC DETECT health outcomes data, integrated with motor vehicle crash report data, inform road safety policies and priorities. Learning Outcomes: Injury control professionals can use syndromic surveillance data to further prevention and practice efforts.